2020
DOI: 10.1111/tbed.13803
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS‐CoV‐2 in pets living with COVID‐19 owners diagnosed during the COVID‐19 lockdown in Spain: A case of an asymptomatic cat with SARS‐CoV‐2 in Europe

Abstract: Pets from COVID‐19 owners were screened for SARS‐CoV‐2 (April‐May 2020). From 23 pets, an asymptomatic cat showed positive RT‐qPCRs results from oropharyngeal swab (negative rectal swab). Remaining pets were negative. This suggests that cats can contract the virus from their infected owners and may act as potential hosts for SARS‐CoV‐2. Their role in carrying live or infectious viruses and disseminating them needs more investigation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 6 publications
14
120
2
Order By: Relevance
“…A study of 919 companion animals in Northern Italy that were sampled at a time of frequent human infection reported that 3.3% of dogs and 5.8% of cats displayed titres of neutralising antibodies [70]. In this study, 69 samples for serology originated from dogs (47) and cats (22) from a known COVID-19 affected household and 12.8% (6/47) of these dogs and 4.5% (1/22) of these cats tested positive for SARS-CoV-2-neutralizing antibodies; in addition, the seroprevalence found in dogs from a known COVID-19 positive household was significantly higher than dogs from COVID-19 negative households (1.5%; 2/133) [70]. Along these lines, a German study of 920 serum samples (which had been collected from domestic cats between April and September 2020 for haematological testing) demonstrated that only 0.69% (6/920) of samples contained antibodies against SARS-CoV-2; two of the positive sera had neutralising antibodies [71], suggesting that human-to-cat transmission might be relatively infrequent.…”
Section: Prevalence Of Sars-cov-2 Infection In Domestic Animalsmentioning
confidence: 85%
See 1 more Smart Citation
“…A study of 919 companion animals in Northern Italy that were sampled at a time of frequent human infection reported that 3.3% of dogs and 5.8% of cats displayed titres of neutralising antibodies [70]. In this study, 69 samples for serology originated from dogs (47) and cats (22) from a known COVID-19 affected household and 12.8% (6/47) of these dogs and 4.5% (1/22) of these cats tested positive for SARS-CoV-2-neutralizing antibodies; in addition, the seroprevalence found in dogs from a known COVID-19 positive household was significantly higher than dogs from COVID-19 negative households (1.5%; 2/133) [70]. Along these lines, a German study of 920 serum samples (which had been collected from domestic cats between April and September 2020 for haematological testing) demonstrated that only 0.69% (6/920) of samples contained antibodies against SARS-CoV-2; two of the positive sera had neutralising antibodies [71], suggesting that human-to-cat transmission might be relatively infrequent.…”
Section: Prevalence Of Sars-cov-2 Infection In Domestic Animalsmentioning
confidence: 85%
“…At the time of writing (30 December 2020), there have been numerous sporadic reports of domestic animals from COVID-19 households that tested positive for SARS-CoV-2 and were presumed to be infected from their owners. Cats infected with SARS-CoV-2 have been identified in Belgium [43], Hong Kong [44], US [45], France [46], Spain [47,48], Germany [49], UK [50], Italy [51], and Switzerland [52], and these cases, as well as cases from Russia, Denmark, Sweden, Chile, Japan, Brazil, and Argentina have been reported to OIE and appear on a list that is regularly updated by OIE [53].…”
Section: Evidence Of Human-to-cat Transmission Of Sars-cov-2mentioning
confidence: 99%
“…Both juvenile and sub‐adult cats did not show any clinical signs, however, cats exhibited tissue tropism, fecal shedding, and seroconversion 33 . In Spain, SARS‐CoV‐2 was detected in an asymptomatic cat of COVID positive owners 34 . Feline enteric coronavirus‐negative adult cats (5–8 years old) of both sexes, upon experimental infection with SARS‐CoV‐2 virus demonstrated virus shedding for 5 days postinfection both orally and nasally and also transmitted infection to naïve cats by contact.…”
Section: Companion Animals As Animal Modelsmentioning
confidence: 97%
“…Since the pandemic began, there have been sporadic cases of SARS-CoV-2 infections in domestic cats around the world. For example, SARS-CoV-2 RNA has been found in 47.1% of 17 tested cats in the USA [ 42 , 43 ], in cats in Belgium, Greece, Switzerland, Brazil [ 20 ], Italy [ 44 ], Hong Kong [ 45 ], France [ 46 ], Canada [ 20 ], Germany, Spain [ 47 , 48 ], Japan [ 20 ], Russia [ 20 ], the Netherlands [ 22 ], and in the UK [ 49 ]. A survey in Chile found that cats appeared to excrete viral RNA for a shorter duration than humans.…”
Section: Sars-cov-2 Infections In Animalsmentioning
confidence: 99%